Comparative Impact Of Corporate Social Responsibility On Marketing Performance: A Study Of ABC PLC And ALEX Industries PLC, Imo State Nigeria. - Nwachukwu, Anthony Nduka; Agu, Agu Godswill (Archives of Business Research, 2018)
The broad aim of this study was to compare the Impact of Corporate Social Responsibility (CSR) on Marketing Performance of a transportation company-Associated Bus Company (ABC) PLC and that of a manufacturing firm- Aluminum Extrusion (ALEX) Industries PLC, all in Imo State. Data were generated from the two companies’ internal and annual reports from 2009 to 2015. Using SPSS version 20 and 21, stated hypotheses were tested with paired sample t-test and simple linear regression. The findings revealed that a significant difference exists on the market share and sales growth of the two firms judging from their corporate social responsibility activities, while no significant difference exists on their financial performance. Again, while CSR exerts positive impact on the market share and sales growth of ABC PLC, the impact on the company’s financial performance was very weak. On ALEX Industries, the findings show that CSR only has positive impact on the company’s market share, the impact on financial performance and sales growth were all negative. With these, the study concluded that the impact of CSR on marketing performance of these two companies differs and recommended among others,that Companies should be consistent in the implementation of their CSR projects because of its positive impact on marketing performance and that CSR should be measured based on its long run effect and not just the short run.